2007
DOI: 10.1142/9789812771995_0003
|View full text |Cite
|
Sign up to set email alerts
|

On entropic characterization of granular materials

Abstract: This chapter presents recent developments in entropic characterization of granular materials. The advantages of the formalism and its use are illustrated for calculation of structural characteristics, such as porosity fluctuations and the throat size distribution. I discuss the relations between the entropic formalism and stress transmission. It is argued that a new sub-ensemble of loading distributions is necessary, which introduces a tensor temperature-like quantity named angoricity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…These constraints lead to a robust conservation law involving the force-moment tensor [4,15,46] of the granular packing,Σ, defined in Eq. 2, which is related to the Cauchy stress tensor [43]σ:…”
Section: Conservation Principlesmentioning
confidence: 99%
“…These constraints lead to a robust conservation law involving the force-moment tensor [4,15,46] of the granular packing,Σ, defined in Eq. 2, which is related to the Cauchy stress tensor [43]σ:…”
Section: Conservation Principlesmentioning
confidence: 99%
“…Concomitant with a given network geometry there is a distribution of contact forces or stresses in the particulate medium. This means that the V-ensemble must be supplemented by the force or stress ensemble (F-ensemble) determined by the contact forces [16,43,44] for a full characterization of jammed matter.…”
Section: Understanding Jammingmentioning
confidence: 99%
“…with the stress σ ij = 1/(2V ) c f c i r c j describing the F-ensemble [16,43,44], where f c i , r c i are the force and position at contact c. For simplicity only the isotropic case is described. Thus, only the pressure σ = σ ii /3 is necessary to describe force fluctuations.…”
Section: Statistical Mechanics Of Jammed Mattermentioning
confidence: 99%
“…In three-dimensional systems of mean coordination number z ) 4 (the marginal rigidity value for grains with high friction coefficients), the number of degrees of freedom per grain is much smaller than the number of quadrons. 8,10 This already suggests that simply summing in the volume function over grains is inaccurate. Indeed, a recent analysis has shown that using the quadrons as the basic "quasiparticles" of the statistical mechanical formalism leads to a better insight than using grains into the role of grain characteristics in forming the structure of a granular system.…”
Section: The Distribution Function Exp (F -H/kt) Is Then Extended To mentioning
confidence: 99%